Occurrence and Antibiotic Resistance of Mesophilic Aeromonas in Three Riverine Freshwaters of Marrakech, Morocco - Boujamaa Imziln (The Scientific World Journal)
I n order to evaluate the impact of pollution and sewage on the occurrence and antibiotic resistance of mesophilic aeromonads in riverine freshwaters of Marrakech, samples were collected from three rivers (Oukaimeden, Ourika, and Tensift) upstream and downstream from the principal bordering villages. During a 2-year study, indicators of pollution increased dramatically in the downstream waters. Bacterial indicators (faecal coliforms and faecal streptococci) correlated with mesophilic aeromonads only in heavily polluted waters. In low and moderately polluted sources, densities of mesophilic aeromonads were independent of water quality indicators and did not correlate statistically with faecal indicators. Average counts of Aeromonas in low and heavily polluted waters were 2.5 × 103 and 2.1 × 106 colony forming units per 100 ml, respectively. The biochemical identification of 841 isolates indicated a predominance of A. caviae in heavily and moderately polluted water and sediment. A. hydrophila was dominant only in low polluted waters and when the temperature was below 12°C. High densities of A. sobria were found in low, moderately polluted, or cleaned waters and when the water temperature was above 18°C. All selected isolates (total = 841) were tested for antibiotic susceptibility against 21 antibiotics. Antibiotic resistance frequencies recorded were: ampicillin and amoxicillin, 100%; novobiocin, 96%; cefalotin, 81%; colistin, 72%; sulfamethoxazole, 40%; cefamandole, 37%; polymyxin B, 23%; trimethoprim, 17%; erythromycin, 15%; streptomycin, 8%; amoxicillin-clavulanate, 5%. Resistance to cefotaxime, kanamycin, gentamycin, chloramphenicol, tetracycline, oxytetracycline, nalidixic acid, rifampicin, or trimethoprim-sulfamethoxazole was found to be <5%. Antibiotic resistance rates did vary according to the source of a strain’s isolation, and high numbers of antibiotic resistant strains were recorded in polluted samples. Since no correlation between mesophilic aeromonads and conventional faecal pollution indicators was observed in low or moderately polluted waters, and since these freshwaters are used for domestic supply, we propose the use of mesophilic aeromonads as complementary water pollution indicators to ensure the safety of water.